Pengaruh temephos terhadap perolehan telur nyamuk Aedes aegypti (L) di cipinang muara jakarta - Mochammad Hasyimi; Suwarto Suwarto; Waluyo Waluyo; Mardiana Mardiana; Suyitno Suyitno; Sukijo Sukijo; Supriyono Supriyono (Perhimpunan Entomologi Indonesia, 2006)
A study on the effect of abaticidal ovitrap on Aedes aegypti egg findings was carried out in Cipinang Muara, East Jakarta from October 1997 until January 1998. Twenty five houses were designed as treatment objects. Ovitrap were sit indoor and outdoor in each house. Seventy five houses were used as buffer. People in this area were trained on how to set up and to manage their ovitrap. Control area in the same